The stronger the better: donor substituents push catalytic activity of molecular chromium olefin polymerization catalysts - Hansen, Helge-Boj; Wadepohl, Hubert; Enders, Markus (Chemistry - a European journal, 2021)
The donor strength of bifunctional pyridine-cyclopentadienyl ligands was altered systematically by the introduction of donating groups in the para-position of the pyridine. In the resulting chromium complexes an almost linear correlation between donor strength and the nitrogen-chromium distance as well as the electronic absorption maximum is experimentally observed. The connection of electron-donating groups in the ligand backbone leads to an efficient transfer of the electronic influences to the catalytically active metal centre without restricting it through steric effects. Therefore, catalytic olefin polymerization activity, which is already very high for the previously studied catalysts, increase considerably by attaching para-amino groups to the chelating pyridine or quinoline, respectively. Combining electron-rich indenyl ligands with para-amino substituted pyridines lead to the highest catalytic activities observed so far for this class of organo chromium olefin polymerisation catalysts. The resulting polymers are of ultra-high molecular weight and the ability of the catalysts to incorporate co-monomers is also very high.